Solvent-driven mono- and bis-sulfenylation of (E)-beta-iodovinyl sulfones with thiols for flexible synthesis of 1,2-thiosulfonylalkenes and 1,2-dithioalkenes - Reddy, Raju Jannapu; Kumari, Arram Haritha; Sharadha, Nunavath; Krishna, Gamidi Rama (Journal of Organic Chemistry, 2022)
The nature of solvent is a key factor for stereoselective mono-and bis-thiolation of (E)-beta-iodovinyl sulfones with thiols under basic conditions. A novel and unprecedented vicinal bisthiolation of (E)-beta-iodovinyl sulfones with thiols under the influence of K2CO3/DMSO at room temperature for quick assembly of (E)-1,2-dithio-1-alkenes is presented. Solvent-induced stereoselective monosulfenylation of (E)-beta-iodovinyl sulfones with thiols has also been established for the synthesis of both (E)- and (Z)-1,2-thiosulfonylethenes in MeCN and MeOH, respectively. Moreover, K2CO3-mediated desulfonylative-sulfenylation of (Z)-1,2-thiosulfonylethenes with thiols in DMSO furnished unsymmetrical (Z)-1,2-dithio-1-alkenes for the first time. The solvent-dependent versatile reactivity of (E)-beta-iodovinyl sulfones has been successfully explored to provide a set of (E)-/(Z)-1,2-dithio-1-alkenes and (E)-/(Z)-1,2-thiosulfonyl-1-alkenes in good to high yields with excellent stereoselectivities. Notably, this operationally simple process utilizes a broad substrate scope with good functional group tolerance and compatibility. The efficacy of the process has been proven for gram-scale reactions, and plausible mechanistic models are outlined on the basis of experimental results and control experiments.